Transcriptome and elemental analysis of the selenium hyperaccumulator Stanleya pinnata and non-accumulator Stanleya elata - Wang, Jiameng, author; Pilon-Smits, Elizabeth, advisor; Sloan, Daniel, committee member; Stargell, Laurie, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Zip file contains data spreadsheet.
Keywords: hyperaccumulation; selenium; Stanleya pinnata; interspecies comparison; gene expression; Stanleya elata